Controllability of solutions for semilinear fractional integrodifferential equations in Banach spaces - Fawzi Mutter Ismaael (Tikrit Journal of Pure Science, 2023)
The study aims to prove the controllability of mild solution for semilinar fractional integerodifferential equations with nonlocal conditions in banach spaces.